Antibacterial Activity and Prebiotic Properties of Six Types of Lamiaceae Honey - Filomena Nazzaro; Maria Neve Ombra; Francesca Coppola; Beatrice De Giulio; Antonio d'Acierno; Raffaele Coppola; Florinda Fratianni (MDPI AG, 2024)
Our work investigated the antimicrobial and prebiotic properties of basil, mint, oregano, rosemary, savory, and thyme honey. The potential antimicrobial action, assessed against the pathogens Acinetobacter baumannii, Escherichia coli, Listeria monocytogenes, Pseudomonas aeruginosa, and Staphylococcus aureus, evidenced the capacity of the honey to influence the pathogenic hydrophobicity and hemolytic activities. Honey inhibited pathogen biofilms, acting especially on the mature biofilms, with inhibition rates of up to 81.62% (caused by the presence of mint honey on L. monocytogenes). S. aureus biofilms were the most susceptible to the presence of honey, with inhibition rates up of to 67.38% in the immature form (caused by basil honey) and up to 80.32% in the mature form (caused by mint honey). In some cases, the amount of nuclear and proteic material, evaluated by spectrophotometric readings, if also related to the honey's biofilm inhibitory activity, let us hypothesize a defective capacity of building the biofilm scaffold or bacterial membrane damage or an incapability of producing them for the biofilm scaffold. The prebiotic potentiality of the honey was assessed on Lacticaseibacillus casei Shirota, Lactobacillus gasseri, Lacticaseibacillus paracasei subsp. paracasei, and Lacticaseibacillus rhamnosus and indicated their capacity to affect the whole probiotic growth and in vitro adhesive capacity, as well as the antioxidant and cytotoxic abilities, and to inhibit, mainly in the test performed with the L. casei Shirota, L. gasseri, and L. paracasei supernatants, the immature biofilm of the pathogens mentioned above.